A systematic review of rehabilitation interventions to prevent and treat depression in post-stroke aphasia. Issue 16 (31st July 2018) - Baker, Caroline; Worrall, Linda; Rose, Miranda; Hudson, Kyla; Ryan, Brooke; O'Byrne, Leana
Abstract: Purpose: Stepped psychological care is the delivery of routine assessment and interventions for psychological problems, including depression. The aim of this systematic review was to analyze and synthesize the evidence of rehabilitation interventions to prevent and treat depression in post-stroke aphasia and adapt the best evidence within a stepped psychological care framework. Method: Four databases were systematically searched up to March 2017: Medline, CINAHL, PsycINFO and The Cochrane Library. Results: Forty-five studies met inclusion and exclusion criteria. Level of evidence, methodological quality and results were assessed. People with aphasia with mild depression may benefit from psychosocial-type treatments (based on 3 level ii studies with small to medium effect sizes). For those without depression, mood may be enhanced through participation in a range of interventions (based on 4 level ii studies; 1 level iii-3 study and 6 level iv studies). It is not clear which interventions may prevent depression in post-stroke aphasia. No evidence was found for the treatment of moderate to severe depression in post-stroke aphasia. Conclusions: This study found some interventions that may improve depression outcomes for those with mild depression or without depression in post-stroke aphasia. Future research is needed to address methodological limitations and evaluate and support the translation of stepped psychological care across the continuum. Implications for Rehabilitation: Stepped psychological care after stroke is a framework with levels 1 to 4 which can be used to prevent and treat depression for people with aphasia. A range of rehabilitation interventions may be beneficial to mood at level 1 for people without clinically significant depression (e.g., goal setting and achievement, psychosocial support, communication partner training and narrative therapy). People with mild symptoms of depression may benefit from interventions at level 2 (e.g., behavioral therapy, psychosocial support and problem solving). People with moderate to severe symptoms of depression require specialist mental health/behavioral services in collaboration with stroke care at levels 3 and 4 of stepped psychological care.